Using Student Teams-Achievement Divisions (STAD) To Improve The Students’ Vocabulary Mastery at MTS. DDI Enrekang - Hasanah, Nurul; Mada Ali, Syahban (Jurnal Ilmiah Multidisiplin Amsir, 2023)
This research aims to find out whether or to find out: Whether or not the use of Student Teams-Achievement Division (STAD) can improve the vocabulary mastery of the students. Whether or not the students have positive attitudes toward cooperative learning type Student Teams-Achievement Divisions (STAD) in learning vocabulary. This research took place at Mts. DDI Enrekang. The kind of this research was Quasi-experimental which have two groups namely experimental and control group. Population of research was the seventh grade students of Mts. DDI Enrekang in academic year 2022/2023 which consisted one class. Sample of the research was 24 in experimental and 24 in control class. The researcher using vocabulary test as instrument of the research. The result showed that there is different result of students who given treatment by STAD and students who given usual technique in teaching vocabulary mastery. The mean score of post-tests for experimental group was higher than the control group (80.83 > 71.25). on the analysis of students’ attitude in following teaching learning process, it was found that the use of STAD influenced the students’ attitudes in learning vocabulary. STAD method helped students’ attitudes turn into positive to improve vocabulary mastery. Most of the students agreed to use of STAD because it could build students’ confidence and work together. Many students also agreed that the use of STAD was interested and active in teaching learning process.